Effects of using ternary gasoline-ethanol-LPO blend on PFI engine performance and emissions. (1st December 2020) - Biswal, Abinash; Gedam, Saurabh; Balusamy, Saravanan; Kolhe, Pankaj
Graphical abstract: Highlights: Ternary blend, G40E20L40, shows similar AFR and calorific value as pure gasoline. Gasoline, ethanol and LPO blend is demonstrated as a drop in fuel for PFI Engine. 60 % utilization of renewable resource based fuels is demonstrated in PFI engine. G40E20L40 with 10 % EGR improves emissions without penalty in Engine performance. Abstract: To date, apart from alcohol, few alternative fuels have been investigated for the operation of port fuel injection (PFI) engines. The current study is examining the suitability of a ternary blend of lemon peel oil (LPO), ethanol, and gasoline as a drop in fuel for traditional gasoline engines. Unique combinations of LPO blends with a calorific value exceeding 40 MJ/kg and stoichiometric air to fuel ratio exceeding 14 are tested on a PFI equipped single-cylinder Kirloskar engine. In this study, two binary blends (G60L40, G80E20) and two ternary blends (G60E20L20, G40E20L40) are prepared on a volume basis and investigated for combustion, performance, and emission characteristics. Combustion stability based exhaust gas recirculation (EGR) rate of 10% is proposed for the ternary blend (G40E20L40). The experimental results showed that the thermodynamic performance of ternary blends is similar to baseline gasoline with a 60% reduction in CO and a 15% reduction in NOx with 10% EGR. Biofuel blends exhibit higher in-cylinder pressure than gasoline due to the higher laminar flame velocities of LPO and ethanol. The ternary G40E20L40 blend with 10% EGR at 3.91 bar BMEP produces higher brake thermal efficiency (BTE) and marginally higher brake specific fuel consumption (BSFC) indicating an insignificant effect on vehicle range on a full tank and good alternative that utilizes 60% renewable fuel with gasoline without any changes to the PFI engine and simultaneously reaping the benefits of significantly improved emissions.